Determinants Of Public Stigma Toward Epilepsy: A Quantitative Analysis - Fonna, Darra Wahyuni; Maulanza, Hady; Fitri, Elfa Wirdani (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2024)
Epilepsy is one of the oldest neurological diseases in the world and ranks second after stroke. Epilepsy is a condition characterized by recurrent seizures due to intermittent brain dysfunction, caused by abnormal and excessive paroxysmal neuronal discharges. Epilepsy has long been widely recognized by society. However, the low level of public knowledge about this disease has led to social stigma, resulting in discrimination against people with epilepsy, which affects the quality of life for both patients and their families. This study aims to identify the factors influencing societal stigma towards epilepsy in Cot Mon Raya Village, Blang Bintang District. The research method used was observational analytics with a cross-sectional approach conducted in May 2024. The study involved 81 respondents selected using simple random sampling. Data were collected through interviews and questionnaires. The results showed that the majority of respondents were in the late elderly age group (56-65 years), most were employed, most had a high school level of education, and most had witnessed a seizure. The majority of respondents did not have relatives with epilepsy, and the average level of knowledge among respondents was good. As for the depiction of stigma towards epilepsy, most respondents had low levels of stigma. The conclusion of the study is that the factors related to societal stigma towards epilepsy are occupation, experience witnessing a seizure, and level of knowledge, while factors such as age, level of education, and having relatives with epilepsy were not related (p>0.05). Based on logistic regression analysis, the most dominant factor influencing societal stigma towards epilepsy is the level of knowledge.